2013
DOI: 10.3346/jkms.2013.28.6.833
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Melanoma Differentiation Associated Gene-7/Interleukin-24 on Invasion In Vitro of Human Melanoma Cancer Cells

Abstract: The acquisition of metastasis potential is a critical point for malignant tumors. Melanoma differentiation associated gene-7/interleukin-24 (mda-7/IL-24) is a potential tumor suppress gene and frequently down-regulated in malignant tumors. It has been implicated that overexpression of MDA-7 led to proliferation inhibition in many types of human tumor. Invasion is an important process which is potential to promote tumor metastasis. However, the role and potential molecular mechanism of mda-7/IL-24 to inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Furthermore, activated PI3K/AKT signaling are involved tumor cell invasion and oncogenesis and this signaling also involved in melanoma cells . More interesting is that the inhibition of the PI3k/Akt pathway led to decrease the invasion of melanoma cells . Results from Figure B also showed that chrysin suppressed the expression of PI3K, p‐AKT(Thr308), p‐AKT(Ser473), and PKC in A375.S2 cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, activated PI3K/AKT signaling are involved tumor cell invasion and oncogenesis and this signaling also involved in melanoma cells . More interesting is that the inhibition of the PI3k/Akt pathway led to decrease the invasion of melanoma cells . Results from Figure B also showed that chrysin suppressed the expression of PI3K, p‐AKT(Thr308), p‐AKT(Ser473), and PKC in A375.S2 cells.…”
Section: Discussionmentioning
confidence: 85%
“…PI3K/Akt is one of the major pathway for tumor invasion, plays a role in MMPs for u‐PA gene regulation, cell survival and cell invasion . AKT activation induce cancer cells invasion and metastasis by stimulates secretions of MMPs …”
Section: Discussionmentioning
confidence: 99%
“…Figure A indicated that Ras, p‐AKT (Thr308) and p‐AKT (Ser473) were reduced in TET treatment at 24 and 48 hours in GBM 8401 cells. The down‐regulation of the PI3k/Akt pathway were associated with the reducing the invasion of melanoma cells . AKT, downstream of PI3K have been reported to be suppressed by the transcription of the E‐cadherin gene .…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway regulated various cellular activities such as proliferation, invasion, metastasis, and death (52). It was suggested that agents to inhibit the MAPK pathway might lead to prevent cancer angiogenesis, proliferation, invasion, and metastasis including melanoma (49,53). Results from western blotting indicated that PEITC and BITC treatment at 24 and 48 h significantly reduced the expression of p-ERK1/2, p-p38 and p-JNK1/2 when compared to control (Fig.…”
Section: Discussionmentioning
confidence: 90%